Marked Arterial Functional Changes in Patients With Arterial Vascular Events Across the Early Adult Lifespan. Issue 6 (June 2020) - Motau, Tshegofatso H.; Norton, Gavin R.; Sadiq, Eitzaz; Manyatsi, Nomvuyo; Kolkenbeck-Ruh, Andrea; Robinson, Chanel; Tade, Grace; Mabena, Philanathi; Monareng, Taalib; Naran, Ravi; Peters, Ferande; Peterson, Vernice; et al.
Abstract : Objective: The age at which arteriosclerosis begins to contribute to events is uncertain. We determined, across the adult lifespan, the extent to which arteriosclerosis-related changes in arterial function occur in those with precipitous arterial events (stroke and critical limb ischemia). Approaches and Results: In 1082 black South Africans (356 with either critical limb ischemia [n=238] or stroke [n=118; 35.4% premature], and 726 age, sex, and ethnicity-matched randomly selected controls), arterial function was evaluated from applanation tonometry and velocity and diameter measurements in the outflow tract. Compared with age- and sex-matched controls, over 10-year increments in age from 20 to 60years, multivariate-adjusted (including steady-state pressures) aortic pulse wave velocity, characteristic impedance (Zc), forward wave pressures (Pf), and early systolic pulse pressure amplification were consistently altered in those with arterial events. Increases in Zc were accounted for by aortic stiffness (no differences in aortic diameter) and Pf by changes in Zc and not aortic flow or wave re-reflection. Multivariate-adjusted pulse wave velocity (7.48±0.30 versus 5.82±0.15 m/s, P <0.0001), Zc ( P <0.0005), and Pf ( P <0.0001) were higher and early systolic pulse pressure amplification lower ( P <0.0001) in those with precipitous events than in controls. In comparison to age- and sex-matched controls, independent of risk factors, pulse wave velocity, and Zc ( P <0.005 and <0.05) were more closely associated with premature events than events in older persons and Pf and early systolic pulse pressure amplification were at least as closely associated with premature events as events in older persons. Conclusions: Arteriosclerosis-related changes in arterial function are consistently associated with arterial events beyond risk factors from as early as 20 years of age. Abstract : Supplemental Digital Content is available in the text.